The Effect of ESG and Green Innovation on the Financial Performance of Listed Firms - Ramadhana, Luqman Arief; Effendi, Syahrul (Research of Finance and Banking, 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) practices and green innovation on corporate financial performance, measured by Tobin's Q. With sustainability gaining prominence globally and in Indonesia evident in the rise of the ESG Leaders Index there remains limited empirical evidence on its financial implications in the Indonesian context. Using purposive sampling, 19 companies listed in the ESG Leaders Index were analyzed from 2020 to 2022. Results show that ESG practices had a negative but insignificant effect on financial performance, whereas green innovation had a positive and significant impact. Additionally, firm size and leverage were found to significantly influence performance. These findings highlight that while ESG implementation in Indonesia faces obstacles such as high costs and limited integration, green innovation presents a more immediate pathway to financial improvement. For managers, this suggests prioritizing environmentally friendly innovation can boost efficiency, reduce costs, and attract sustainability-minded stakeholders. Meanwhile, ESG practices should be approached with a strategic, long-term mindset to realize their potential value. Sustainability should be embraced not merely as compliance but as a forward-looking investment contributing to long-term profitability.